Stability study of Algerian Nigella sativa seeds stored under different conditions - Ahamad Bustamam, Muhammad Safwan; Hadithon, Kamarul Arifin; Mediani, Ahmed; Abas, Faridah; Rukayadi, Yaya; Lajis, Nordin; Shaari, Khozirah; Ismail, Intan Safinar (Hindawi Publishing Corporation, 2017)
In a study to determine the stability of the main volatile constituents of Nigella sativa seeds stored under several conditions, eight storage conditions were established, based on the ecological abiotic effects of air, heat, and light. Six replicates each were prepared and analyzed with Headspace-Gas Chromatography-Mass Spectrometry (HS-GC-MS) for three time points at the initial (1st day (0)), 14th (1), and 28th (2) day of storage. A targeted multivariate analysis of Principal Component Analysis revealed that the stability of the main volatile constituents of the whole seeds was better than that of the ground seeds. Exposed seeds, whole or ground, were observed to experience higher decrement of the volatile composition. These ecofactors of air, heat, and light are suggested to be directly responsible for the loss of volatiles in N. sativa seeds, particularly of the ground seeds.